A MGinf Queue Busy Period Distribution Characterizing Parameter - Ferreira, M. A. M. (arXiv:2110.03457, 2025)
In this work it is proposed a parameter, η, to characterize the MGinf Queue Busy Period distribution that is a modification of the peakedness proposed in Whitt (1984). As this distribution moments centered at the origin are given, in general, by very complex expressions it is relevant to search for parameters simpler but with good descriptive properties.